2020
DOI: 10.1242/jeb.237289
|View full text |Cite
|
Sign up to set email alerts
|

The ander's organ: a mechanism for anti-predator ultrasound in a relict orthopteran

Abstract: The use of acoustics in predator evasion is a widely reported phenomenon amongst invertebrate taxa, but the study of ultrasonic anti-predator acoustics is often limited to the prey of bats. Here, we describe the acoustic function and morphology of a unique stridulatory structure – the Ander's organ – in the relict orthopteran Cyphoderris monstrosa (Ensifera, Hagloidea). This species is one of just eight remaining members of the family Prophalangopsidae, a group with a fossil record of over 90 extinct species w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…2G and 2H ). We carried out experiments in which these spinules were covered with a layer of wax to test whether these structures can be used in stridulation, like the Ander’s organs of Cyphoderris monstrosa (Prophalangopsidae) ( Woodrow et al, 2021 ) or abdominal fields with tubercules of representatives of Anostostomatidae ( Zhantiev, Kalinkina & Korsunovskaya, 1982 ) and Gryllacrididae ( Field & Bailey, 1997 ). They showed that the insects in this case were capable to emit wing protest signals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2G and 2H ). We carried out experiments in which these spinules were covered with a layer of wax to test whether these structures can be used in stridulation, like the Ander’s organs of Cyphoderris monstrosa (Prophalangopsidae) ( Woodrow et al, 2021 ) or abdominal fields with tubercules of representatives of Anostostomatidae ( Zhantiev, Kalinkina & Korsunovskaya, 1982 ) and Gryllacrididae ( Field & Bailey, 1997 ). They showed that the insects in this case were capable to emit wing protest signals.…”
Section: Resultsmentioning
confidence: 99%
“…Mechanisms for producing these sounds are different: males with a developed tegminal sound apparatus produce them in response to mechanical stimulation. Sounds of this kind, loud and prolonged, are, as in katydids of the tribe Zichyini ( Zhantiev, Korsunovskaya & Byzov, 1995 ; Elaeva & Korsunovskaya, 2012 ), apparently aimed at scaring away predators ( Masters, 1980 ; Low, Naranjo & Yack, 2021 ; Woodrow et al, 2021 ). Wing protest signals are emitted by both males, and females.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency response of the tympana was measured in seven female and 11 male specimens of C. monstrosa, totalling 36 individual ears of which 33 provided suitable data for analysis. Specimens were immobilized using a unique method under previous protocols [ 34 ]; by freezing at −2°C for 2 min. They were then mounted in a natural orientation to a copper platform with wax made of 50% beeswax (Fisher Scientific, Loughborough, UK) and 50% colophonium (Sigma-Aldrich Company Ltd, Dorset, UK).…”
Section: Methodsmentioning
confidence: 99%
“…Reduced flight is a well-established evolutionary mechanism to reduce or avoid predation by aerial predators, and in particular, bats [26]. The other extant species in this family, all of whom have lost the ability to fly, exhibit novel anti-predator defences, namely ultrasonic sound production organs [27], which likely evolved to act as a deterrent to a new host of predators they now face after switching to a terrestrial lifestyle. Such anti-predator adaptations are not present in P. obscura, nor are any other morphological adaptations associated with predation by bats such as enlarged cuticular spines [26].…”
Section: Plos Onementioning
confidence: 99%